Children's Social Care and Early Intervention Policy in England - Dan Anderberg; Christina Olympiou (Center for Economic Studies and ifo Institute (CESifo), 2020)
We study the relationship between a key early intervention policy designed to support families with children up to the age of four and the rate at which children are taken into social care. The gradual build-up of over 3,600 Sure Start Children's Centres (SSCC), operated by Local Authorities across England, created large spatial and cohort variation in the provision of a range of services that include childcare, early education, health and parenting support. Local Authorities are also responsible for the safeguarding of children and about 25 children per 10,000 are taken into social care annually, in the majority of cases to protect them from abuse and neglect. We find that SSCC provision is associated with a higher rate of entry into care for children aged 0-4, but a lower rate of entry for children aged 5-9. The findings are consistent with the policy improving longer-term outcomes while identifying cases in urgent need of care.
Keywords: I38; J12; J13; 330; social care for children; early intervention; abuse and neglect